2005
DOI: 10.2174/1381612053507837
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Blood-Spinal Cord Barrier in Traumatic Injury and Repair

Abstract: Blood-spinal cord barrier (BSCB) plays an important role in the regulation of the fluid microenvironment of the spinal cord. Trauma to the spinal cord impairs the BSCB permeability to proteins leading to vasogenic edema formation. Several endogenous neurochemical mediators and growth factors contribute to trauma induced BSCB disruption. Studies carried out in our laboratory suggest that those drugs and neurotrophic factors capable to attenuate the BSCB dysfunction following trauma are neuroprotective in nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
218
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(227 citation statements)
references
References 272 publications
(480 reference statements)
8
218
0
Order By: Relevance
“…128 In vivo disease models If in the previous examples the integrity of the BBB was maintained and the brain was considered as a "non-pathologic" brain, in the following examples, several researches have been reviewed concerning neuro-pathologies in which the BBB integrity and permeability is seriously compromised. 12,51,103,135 These pathologies could vary from neurodegenerative diseases (Parkinson, Alzheimer and Huntigton's) to epilepsy, infectious brain diseases, strokes and many others.…”
Section: Nanoparticles and Liposomesmentioning
confidence: 99%
“…128 In vivo disease models If in the previous examples the integrity of the BBB was maintained and the brain was considered as a "non-pathologic" brain, in the following examples, several researches have been reviewed concerning neuro-pathologies in which the BBB integrity and permeability is seriously compromised. 12,51,103,135 These pathologies could vary from neurodegenerative diseases (Parkinson, Alzheimer and Huntigton's) to epilepsy, infectious brain diseases, strokes and many others.…”
Section: Nanoparticles and Liposomesmentioning
confidence: 99%
“…11 An investigation has been done to evaluate macromolecular transport structures that increased after the brain and spinal cord had been subjected to a variety of injuries. A theory was hypothesized that a unique endothelial cell system formed transendothelial cell channels defined as vesiculo-canalicular or vesiculo-tubular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Since spinal cord injury increases permeability of the blood-spinal cord barrier, 23,24 it is reasonable to consider whether p-glycoprotein inhibition is necessary to increase methylprednisolone concentrations in the injured spinal cord. However, Braughler and Hall demonstrated that methylprednisolone entry into injured spinal tissue was greater than in uninjured tissue only if methylprednisolone was administered within 1 h of injury.…”
Section: Discussionmentioning
confidence: 99%